ANALISIS KEBUTUHAN PENGEMBANGAN MODEL PEMBELAJARAN DALAM UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KEPEDULIAN LINGKUNGAN SISWA KELAS X SMA N 3 RAMBAH HILIR - asra, azmi; Amrizaldi, Amrizaldi (Jurnal Edu Research, 2025)
This study aims to conduct a needs assessment as a preliminary stage in the development of an instructional model. The urgency of this research arises from the gap between the demands of 21st-century competencies particularly critical thinking skills and the need to strengthen environmental concern as part of Education for Sustainable Development (ESD), compared to actual classroom practices. The study employed a mixed-methods approach with a sequential exploratory design, integrating quantitative and qualitative data. Quantitative data were collected through a critical thinking skills test and an environmental concern questionnaire administered to 33 tenth-grade students at SMA N 3 Rambah Hilir. Qualitative data were obtained through teacher interviews and classroom observations. The findings indicate that students’ critical thinking skills were predominantly at a moderate level (54.55%), while only 27.27% reached a high level, with notable weaknesses in evaluation (21.21%) and self-regulation (18.18%) indicators. Similarly, students’ environmental concern was mostly categorized as moderate (51.52%), with low levels of participation and pro-environmental behavior (18.18%), despite relatively strong environmental attitudes (45.45%). These results suggest that existing instructional practices have not effectively fostered higher-order critical thinking or translated environmental awareness into concrete actions. Therefore, the findings provide a strong empirical foundation for developing a contextual and reflective instructional model integrated with local wisdom to enhance both critical thinking skills and environmental concern.